Rehabilitation of Degraded Land using Paddy Straw Compost and Peat for Agriculture Purposes - SANTUN R.P SITORUS; H SOEWANDITA (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2010)
The objectives of the research were to study: (1) the influence of peat and paddy straw compost on crop growth and production, and (2) the influence of residual effect of peat and paddy straw compost application on soil chemical characteristics. The research was conducted at Cikembang, Sukabumi; Cikabayan, Kampus IPB Darmaga, Bogor; and Rasau Jaya,Pontianak, respectively. Soil analysis was conducted at soil laboratory of Department of Soil Science and Land Resource, IPB and Soil Research Centre, Bogor. The research area was degraded grass land located at 300 m above sea level with slope less than 15%. Factorial Design with two replications was used with soybean var. Slamet as an indicator crop. Treatments comprise peat and paddy straw compost, each with five dosesi.e. for peat : 0 t ha-1, 7 t ha-1, 14 t ha-1, 21 t ha-1, and 28 t ha-1, respectively and for paddy straw compost 0 t ha-1, 10 t ha-1, 20 t ha-1, 30 t ha-1, and 40 t ha-1. Observation was carried out for crop height, grain dry weight, and soil chemical characteristics after harvesting. The results showed that application of peat and paddy straw compost significantly increased crop height and production of soya bean. Application of single 40 t ha-1 paddy straw compost significantly increase the highest grain dry weight. The rehabilitation effort was also increase soil fertility status. Residue of paddy straw compost and peat application was significantly increase soil chemical characteristics i.e.: organic-C, N, P2O5, K2O, Ca, Mg, and Base saturation of the soil. The highest N, P2O5, K2O, Ca, Mg, CEC, and base saturation of the soil was found in application of single paddy straw with doses of 40 t ha-1. Application of paddy straw compost fordegraded land increased soya bean production and rehabilitated of soil condition better than application of peat.